Hydromorphological assessment of the lower Hungarian Drava section and its floodplain - Lóczy , Dénes; Dezső, József; Czigány, Szabolcs; Pirkhoffer, Ervin (Acta Geographica Debrecina Landscape & Environment series, 2016)
The hydromorphological properties of rivers and their floodplains receive increased attention both in basic research and water management. A comparison of hydromorphological parameters before and after river regulation (involving floodplain drainage) provides important information for river management, particularly floodplain rehabilitation. The paper assesses a selected reach of the Drava River and the corresponding floodplain utilising two international approaches, the REFORM framework and the Italian Morphological Quality Index.